Barriers to Successful Early Infant Diagnosis of HIV Infection at Primary Care Level in Malawi. Issue 3 (March 2015) - Cromwell, Elizabeth A.; Dow, Anna E.; Low, Daniel; Chirambo, Chawanangwa; Heyderman, Robert S.; Dube, Queen; Van Rie, Annelies
Abstract : HIV-infected women seeking early infant HIV diagnosis (EID) services in Malawi were asked about factors potentially associated with returning for EID results. Many (33.3%) infants failed to complete the EID process because of time and costs required for multiple visits. Infants of mothers receiving antiretroviral treatment were less likely to drop out (adjusted risk ratio 0.51), suggesting that EID completion may improve in programs providing antiretroviral treatment to all pregnant women. Abstract : Supplemental Digital Content is available in the text.